Postbrushing and fine‐needle aspiration biopsy follow‐up and treatment options for patients with pancreatobiliary lesions: The papanicolaou society of cytopathology guidelines. Issue 4 (April 2014) - Kurtycz, Daniel; Tabatabai, Z. Laura; Michaels, Claire; Young, Nancy; Schmidt, C. Max; Farrell, James; Gopal, Deepak; Simeone, Diane; Merchant, Nipun B.; Field, Andrew; Pitman, Martha Bishop; Michael, Claire W.
<x xml:space="preserve">Abstract</x> The papanicolaou society of cytopathology (PSC) has developed a set of guidelines for pancreatobiliary cytology including indications for endoscopic ultrasound (EUS) guided fine‐needle aspiration (FNA) biopsy, techniques of EUS‐FNA, terminology and nomenclature for pancreatobiliary cytology, ancillary testing, and postprocedure management. All documents are based on the expertise of the authors, a review of the literature, discussions of the draft document at several national and international meetings over an 18 month period and synthesis of online comments of the draft document on the PSC web site [www.papsociety.org]. This document selectively presents the results of these discussions and focuses on the follow‐up and treatment options for patients after procedures performed for obtaining cytology samples for the evaluation of biliary strictures and solid and cystic masses in the pancreas. These recommendations follow the six‐tiered terminology and nomenclature scheme proposed by Committee III. Diagn. Cytopathol. 2014;42:363–371. © 2014 Wiley Periodicals, Inc.